Going Beyond the First Child : Analysis of Russian Mothers' Desired and Actual Fertility Patterns - Levin, Victoria; Besedina, Elena; Aritomi, Tami (World Bank, Washington, DC, 2016)
The Russian Federation's population has been declining since 1992, but recently the decline appears to be over. Although fertility has risen since the 2007 introduction of the family policy package, which focused on stimulating second and higher-order births, total fertility rates still remain significantly below replacement rate. Unlike some Western European countries, low overall fertility in Russia can be explained predominantly by a high prevalence of one-child families, despite the two-child ideal family size reported by the majority of Russians. This paper examines the correlates of Russian first-time mothers' desire and decision to have a second child. Using the 2004–12 waves of the Russia Longitudinal Monitoring Survey, the study focuses on the motherhood-career trade-off as a potential obstacle to higher fertility in Russia. The preliminary results indicate that among Russian first-time mothers, being in stable employment is positively associated with the likelihood of having a second child. Moreover, the desire to have a second child is positively associated with the first child attending formal childcare, which suggests that the availability, affordability, and quality of such childcare can be important for promoting fertility. These results are broadly consistent with previous studies in other European countries that indicate that the ability of mothers to combine work and family has important implications for fertility, and that pro-natalist policies focusing on childcare accessibility can offer the greatest payoffs. In addition to these factors, better housing conditions, being married, having an older child, and having a first-born boy are also positively associated with having a second child.